Correlation Analysis between Income Level, Discounts and Unplanned Purchases in Urban Communities - Mariyanih Mariyanih; Pitri Yandri (JMB : Jurnal Manajemen dan Bisnis, 2026)
The purpose of this study is to analyze the relationship between income levels, discounts, and unplanned purchases in urban communities in South Tangerang. Where the consumer phenomenon is often found in urban communities characterized by high incomes and the large amount of advertising exposure makes people tend to be easily stimulated by marketers, because currently shopping is not only to fulfill life's needs but has become a lifestyle. This study is quantitative in the use of association with data collection instruments using questionnaires given to 60 respondents. Sampling was carried out using a nonprobability sampling method with a purposive sampling technique with the following criteria: a). respondents are female, b). respondents have an age range of 23-50 years, and c). Respondents have made unplanned purchases both e-commerce and non-e-commerce. With data analysis used is product moment through the SPSS program version 25. The results of this study indicate that the variable Income Level with Unplanned Purchases has a positive and significant relationship, this relationship occurs because of the tendency of a high lifestyle and is also supported by easy access to shopping. In addition, discounts and unplanned purchases have a positive and significant relationship because people are easily tempted to make unplanned purchases on products that have big discounts.